Physical discomfort in early pregnancy and postpartum depressive symptoms. (3rd April 2019) - Ertmann, Ruth K.; Nicolaisdottir, Dagny R.; Kragstrup, Jakob; Siersma, Volkert; Lutterodt, Melissa C.; Bech, Per
Abstract: Purpose : Pregnancy examinations conducted in general practice focus mainly on identifying high-risk pregnancies and pregnancy complications. The pregnancy health record has a biomedical focus, and consequently the woman's mental well-being may receive less attention. The aim of this study was to evaluate the extent to which early pregnancy-related symptoms should be considered as indicators of an increased risk of postpartum depression. Materials and methods : For a prospective cohort of 1508 pregnant women, the presence of 11 pregnancy-related symptoms was recorded at the first prenatal care consultation together with background information about socio-demography and health. Depression was assessed 8 weeks postpartum with the major depression inventory (MDI) and depression was considered present if MDI > 20. Multivariable logistic regression was used to assess the association between pregnancy-related symptoms and postpartum depressive symptoms, and to adjust for potential confounders. Results : A high depression score (MDI score >20) 8 weeks postpartum was found among 6.6% of the women and showed apparent associations with physical discomfort in early pregnancy, such as back pain and pelvic cavity pain. Analysis of confounding revealed, however, that signs of vulnerable mental health, present in early pregnancy, explained most of these associations. Conclusions : Indicators of an increased risk of postpartum depressive symptoms may be found in early pregnancy. Pregnancy-related pain in the first trimester may be a sign of psychological vulnerability or an aspect of an existing depressive state that calls for attention.